2014
DOI: 10.1007/s12013-014-0361-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Val108/158Met COMT Gene Polymorphism on the Efficacy of Modified Electroconvulsive Therapy in Patients with Treatment Resistant Depression

Abstract: Depression is a common emotional disorder associated with increased risk of suicide and rate of disability. In this double-blinded control study, we tested the efficacy of modified electroconvulsive therapy (MECT) in patients with treatment resistant depression (TRD) using the Hamilton Depression Rating Scale for Depression (HAMD). The total scores of HAMD were found to be significantly decreased after the treatment. The genotyping of catechol-O-methyltransferase (COMT) was carried out with polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…COMT is responsible for one of the major catabolic pathways of monoamines. Variants in this gene were associated with increased risk of suicide in TRD (Schosser et al, 2012a), they were observed more frequently in TRD compared with healthy controls (Lin et al, 2015), and they may be associated with ECT response in TRD (Domschke et al, 2010). On the other hand, negative results were also reported (Malaguti et al, 2011; Fabbri et al, 2014).…”
Section: Overview Of Previous Findingsmentioning
confidence: 99%
“…COMT is responsible for one of the major catabolic pathways of monoamines. Variants in this gene were associated with increased risk of suicide in TRD (Schosser et al, 2012a), they were observed more frequently in TRD compared with healthy controls (Lin et al, 2015), and they may be associated with ECT response in TRD (Domschke et al, 2010). On the other hand, negative results were also reported (Malaguti et al, 2011; Fabbri et al, 2014).…”
Section: Overview Of Previous Findingsmentioning
confidence: 99%
“…A study examining the functional COMT val158met polymorphism in 119 patients with TRD found that the enzymatically more active COMT val/val genotype carriers treated with ECT were more often responders than non-responders (Anttila et al, 2008). This finding was replicated in a sample of 100 Chinese patients undergoing ECT for TRD (Lin et al, 2014). Domschke et al (2010) also confirmed these findings in a sample of 104 patients with TRD, finding that the COMT 158 val allele was associated with a superior response to ECT in female Caucasian patients.…”
Section: Catechol-o-methyltransferase and Dopamine Receptor Genesmentioning
confidence: 73%
“…A study examining the functional COMT val158met polymorphism in 119 patients with TRD found that the enzymatically more active COMT val/val genotype carriers treated with ECT were more often responders than non‐responders (Anttila et al ., ). This finding was replicated in a sample of 100 Chinese patients undergoing ECT for TRD (Lin et al ., ). Domschke et al .…”
Section: Introductionmentioning
confidence: 97%
“…In short, in the elderly (Husain et al, 2004), psychotic symptom comorbidities (Husain et al, 2004), postpartum depression (Rundgren et al, 2018), shorter episode duration and more severe depressive symptoms (van Diermen et al, 2018), early depression alleviation (Birkenhager et al, 2019), lower NAA levels in the dACC at baseline (Njau et al, 2017), low genetic risk load (Foo et al, 2019), genetic or epigenetic modifications (Huuhka et al, 2007;Kleimann et al, 2015;Lin et al, 2015), and high baseline serum IL-6 levels (Kruse et al, 2018) and a serum MM-9 profile (Shibasaki et al, 2018) were more likely to benefit ECT recipients. Moreover, the subfield index of hippocampus and neural network plasticity (Abbott et al, 2014;Ota et al, 2015;van Waarde et al, 2015;Redlich et al, 2016;Cao et al, 2018;Nuninga et al, 2019) may provide precise evidence to predict the outcome.…”
Section: Prediction Of Response and Relapse To Ect Bioinformaticsmentioning
confidence: 99%